Conflict of Deciding Zero Point Kilometer on Islamic Entrance in Indonesian Archipelago (Critical Discourse Analysis with Norman Fairclough Approach) - Husniah Ramadhani Pulungan; Sumarlam Sumarlam (Karsa: Journal of Social and Islamic Culture, 2017)
Critical discourse analysis (CDA) in this research came from two texts of online news. They were Medan Business Daily from Medan, North Sumatera and Kabar Pidie Jaya from Pidie, Aceh. Both of the news had the same theme, that was legitimation zero point kilometer of Islamic entrance in Indonesian archipelago. However, both of the news was conflicated, if it had not been finished as soon as possible, it would be a long conflict. Because of that, this CDA had a purpose to try for giving solution from another point of view. The point of view was from historical data about differences of point of view on the online news. The method of this study was by using Norman Fairclough approach with text analysis (description), discourse practice (interpretation), and social practice (explanation). The result of text analysis (description) was analyzed by using rhetoric pattern; modality, such as akan, bisa; positive sentences; negative sentences; interrogative sentences; experiential and attitudinal vocabularies; life metaphor. Discourse practice analysis (interpretation) such as event series from the two online news texts. Explanative analysis followed the situational change, institution change, and social-cultural change which would be mediating this conflict based on the historical facts. Copyright (c) 2017 by KARSA. All right reserved DOI: 10.19105/karsa.v25i1.1223